Strategies for Identifying Sheng: What counts as Sheng? - Githinji, Peter (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The purpose of this paper is to look at different characteristics of Sheng that distinguishes it from other linguistics codes and specifically Standard Swahili. A loose application of the markedness theory will be used to show the elements that distinguishes Sheng from Standard Swahili. Sound segments, some prosodic features, morphological and lexical elements are examined and contrasted with those of their donor languages to identify the marked sounds that are regarded as markers of Sheng. These innovations are attributed to borrowing from various languages. The structural deviation and semantic shift of familiar words in Swahili and other languages is seen as another manifestation of markedness that qualifies those forms as Sheng. The paper concludes by calling for the expansion of the field of study of youth and urban languages to pay more attention to the linguistic areas that have not received adequate attention in order to provide a complete account of these languages.